Getting the girl - Zusak, Markus (New York : Push, 2004)
Tired of being the underdog, Cameron Wolfe hungers to become something worthwhile and finally finds a girl with whom he can share his words and feelings--his popular brother Rube's ex-girlfriend.
Originally published in Australia as: When dogs cry.
Sequel to: Fighting Ruben Wolfe.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Brothers -- Fiction; Interpersonal relations -- Fiction; Man-woman relationships -- Fiction; Self-actualization (Psychology) -- Fiction; Brothers -- Fiction; Interpersonal relations -- Fiction; Man-woman relationship -- Fiction; Self-realization -- Fiction